Thoracoscopic management of post-operative chylothorax: Clipping of the thoracic duct and pleuroperitoneal shunt - Riveros, Youry (2005)
Chylothorax by thoracic duct injury is a catastrophic and rare complication that takes place following cardiac operations, chest surgery and extensive neck dissection. The chyle daily loss may lead to nutritional, metabolic and immunologic deficiencies, and even death if not treated. Currently, early surgical treatment is recommended with support of video-assisted thoracic surgery (VATS) applying clips, endostapler or ultrasonic coagulator over the thoracic duct. Conservative management has a great percentage of failures mainly due to high output chylous fistulae. We report the successful treatment of a patient with chylothorax following chest surgery for a lung giant hydatidic cyst, by clipping of the thoracic duct and pleuroperitoneal shunt.